FRI0353 Association of Attitudes Toward Conventional Synthetic Disease-Modifying Anti-Rheumatic Drugs and Tumor Necrosis Factor Inhibitors and Treatment Adherence in Rheumatoid Arthritis, Ankylosing Spondylitis, and Psoriatic Arthritis: Results from the Global Align Study. (9th June 2015) - Smolen, J.S.; Gladman, D.; McNeil, H.P.; Weinman, J.; Kalus, S.; Dorr, A.; Hojnik, M.; Nurwakagari, P.; Selenko-Gebauer, N.
Abstract : Background: In rheumatic diseases, adherence to therapy is critical to optimize patient outcomes and may be influenced by patients' beliefs about medication. 1-3 However, little information is available on the association between adherence to medications and necessity beliefs and concerns toward conventional synthetic disease-modifying anti-rheumatic drugs (csDMARD) and tumor necrosis factor inhibitors (TNFi) in rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA). Objectives: The multi-country, cross-sectional ALIGN study determined patients' specific and general beliefs towards medications and adherence to selected systemic therapies in 6 immune-mediated inflammatory diseases (IMIDs). This analysis explored the association of attitudes and adherence in relation to csDMARD and TNFi in patients with RA, AS, and PsA. Methods: During a routine visit, the Beliefs About Medicines Questionnaire (BMQ) 4 and 4-item Morisky Medication Adherence Scale (MMAS-4) 5 were administered to >7000 adult patients diagnosed with IMIDs who were being treated with csDMARD, steroids, nonsteroidal anti-inflammatory drugs (NSAID), and/or TNFi. The associations were assessed by multiple linear and logistic regression models. Results: 3390 patients were analyzed (RA, n=1943; AS, n=812; PsA, n=635; female, 63%; mean age, 51 y). Depending on the treatment, the percentage of patients with high adherence (MMAS-4 score of 4) was 53%–76%, 29%–71%, and 47%–100% in patients with RA, AS, and PsA, respectively. In all 3 indications, TNFi treatment within the TNFi+csDMARD combination therapy was associated with higher BMQ-specific necessity beliefs vs csDMARD treatment within csDMARD ± steroid therapy (the reference). Across all 3 indications, higher necessity beliefs were associated with higher treatment adherence. TNFi treatment appeared to have an additional positive effect on treatment adherence in RA and AS, but not in PsA (Table of logistic regression results for treatments). Conclusions: ALIGN is the first large study to explore attitudes and treatment adherence towards systemic medication across 3 rheumatologic diseases. A direct positive association of TNFi treatment with necessity beliefs was seen, which in turn appeared to modulate treatment adherence. Confirmatory studies are needed. References: Contreras-Yanez I, et al. Am J Med Sci. 2010;340(4):282-290. Bluett J, et al. Rheumatology (Oxford). 2014. [Epub ahead of print.] Horne R, et al. PLoS ONE. 2013;8(12):e80633. Horne R, et al. Psychol Health. 1999;14:1-24. Morisky DE, et al. Med Care. 1986;24(1):67-74. Acknowledgements: AbbVie funded the study and the analysis, and approved the abstract for submission. Medical writing assistance was provided by Michael Theisen of Complete Publication Solutions, LLC, and was supported by AbbVie. The authors thank Fabrice Gillas, MD, of AbbVie for his contributions to the ALIGN study. Disclosure of Interest: J. Smolen Grant/research support from: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo Nordisk, Roche, Sandoz, and UCB, Consultant for: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo Nordisk, Roche, Sandoz, and UCB, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB., H. P. McNeil: None declared, J. Weinman Employee of: Atlantis Healthcare, S. Kalus Employee of: GKM Gesellschaft fuer Therapieforschung mbH, A. Dorr Shareholder of: AbbVie, Employee of: AbbVie, M. Hojnik Shareholder of: AbbVie, Employee of: AbbVie, P. Nurwakagari Shareholder of: AbbVie, Employee of: AbbVie, N. Selenko-Gebauer Shareholder of: AbbVie, Employee of: AbbVie